Role of specialized composition of SWI/SNF complexes in prostate cancer lineage plasticity - Joanna Cyrta (Nature Portfolio, 2020)
The differentiation of prostate adenocarcinoma to neuroendocrine prostate cancer (CRPC-NE) is a mechanism of resistance to androgen deprivation therapy. Here the authors show that SWI/SNF chromatin-remodeling complex is deregulated in CRPC-NE and that the complex interacts with different lineage specific factors throughout prostate cancer transdifferentiation.